Transforming Engineering Education with Hands-On Robotics: The IEEE RAS-UNB Experience - Pastrana, M. A.; Gomes, Nícolas Y.; Baptista, Roberto De Souza; Muñoz, Daniel M. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
The growing disinterest of engineering stu-dents in control theory and robotics, combined with the gap between theory and practice in traditional teaching methods, motivated the creation of an innovative approach by the IEEE RAS student chapter at the University of Brasilia. The goal was to develop and imple-ment a practical STEM-based methodology integrating teaching, research, and outreach through the use of real, accessible robotic platforms. The methodology was applied in four distinct projects-VSSS, EVAIMARIA, Edubot, and UnBeatables-involving undergraduate and graduate students in activities such as prototype con-struction, participation in robotics competitions, and scientific production. As a result, there was a significant increase in student engagement, membership growth, the publication of seven papers at IEEE international conferences, and the development of low-cost educational robots with high replicability potential. The implemented methodology proved effective in promoting interest in the field and can be adapted by other institutions, contributing significantly to strengthening engineering education and training new researchers.